2008
DOI: 10.1093/jac/dkn380
|View full text |Cite
|
Sign up to set email alerts
|

UK epidemic Escherichia coli strains A-E, with CTX-M-15  -lactamase, all belong to the international O25:H4-ST131 clone

Abstract: Objectives: Uropathogenic and invasive Escherichia coli O25:H4-ST131 isolates producing CTX-M-15 extended-spectrum b-lactamase (ESBL) enzymes have recently been shown to be disseminated across the globe. In the UK, many CTX-M-15 ESBL-producing E. coli strains have been previously defined as belonging to the epidemic strains A -E, as determined by PFGE. The present study was carried out to define the relationship between these two groups of pathogenic E. coli.Methods: Multilocus sequence typing and PFGE were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
103
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 9 publications
9
103
3
4
Order By: Relevance
“…Characterization of the bla genes revealed that half of the isolates are bla CTX-M-15 positive. This finding demonstrates the emergence of this ESBL type in the Netherlands and confirms previous studies that reported the emergence of this gene worldwide (1,2,10,20).…”
Section: Discussionsupporting
confidence: 91%
“…Characterization of the bla genes revealed that half of the isolates are bla CTX-M-15 positive. This finding demonstrates the emergence of this ESBL type in the Netherlands and confirms previous studies that reported the emergence of this gene worldwide (1,2,10,20).…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have demonstrated the clonal expansion of certain enterobacterial clones that are able to acquire plasmids harbouring different ESBLs and plasmidic AmpCs [8]. The high prevalence of bla ESBL genes in different parts of the world is caused by the horizontal transfer of plasmids among unrelated clones and also within local or international epidemic clones.…”
Section: Introductionmentioning
confidence: 99%
“…The antibiotic resistance profiles of these STs differ markedly: members of STs 69, 73, and 95 remain largely susceptible to antibiotics and rarely have resistance to extended-spectrum cephalosporins in particular, whereas members of ST131 show increasing resistance to multiple antibiotic classes and account for 80 to 90% of multiresistant ExPEC infections (10,12,13). In particular, ST131 isolates often carry CTX-M-type extended-spectrum ␤-lactamases (ESBLs), together with fluoroquinolone and aminoglycoside resistances (13)(14)(15)(16).…”
mentioning
confidence: 99%